2023
DOI: 10.3390/molecules28093848
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Melt Extrusion as an Effective Technique for Obtaining an Amorphous System of Curcumin and Piperine with Improved Properties Essential for Their Better Biological Activities

Abstract: Poor bioavailability hampers the use of curcumin and piperine as biologically active agents. It can be improved by enhancing the solubility as well as by using bioenhancers to inhibit metabolic transformation processes. Obtaining an amorphous system of curcumin and piperine can lead to the overcoming of these limitations. Hot-melt extrusion successfully produced their amorphous systems, as shown by XRPD and DSC analyses. Additionally, the presence of intermolecular interactions between the components of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 56 publications
4
24
0
Order By: Relevance
“…In addition, the carbonyl peak of PVP K30 shifted from FT-IR spectra of the various systems investigated are presented in Figure 7. The differences between the crystalline and amorphous spectra of curcumin and hesperetin have already been described [42,43].…”
Section: Resultsmentioning
confidence: 92%
“…In addition, the carbonyl peak of PVP K30 shifted from FT-IR spectra of the various systems investigated are presented in Figure 7. The differences between the crystalline and amorphous spectra of curcumin and hesperetin have already been described [42,43].…”
Section: Resultsmentioning
confidence: 92%
“…PVP acts as a hydrophilic polymer that can form a stable molecular dispersion with polyphenols, thereby preventing their crystallization and maintaining them in an amorphous state. It was confirmed that the amorphous form of the polyphenols has a significantly higher solubility compared to its crystalline counterpart [ 45 , 46 , 48 , 55 , 56 , 57 , 58 ]. Therefore, this study attempts to obtain an amorphous solid dispersion (ASD) of myricetin (MYR, Figure 1 b) with PVP K30 (PVP30).…”
Section: Resultsmentioning
confidence: 99%
“…Amorphous materials lack long-range order in their atomic arrangement, while crystalline materials exhibit a regular and repeating pattern. Confirming the amorphous/crystalline nature of a substance is crucial as it affects its physical and chemical properties, including solubility, stability, and bioavailability [ 46 , 47 , 48 , 50 , 55 , 56 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations